Analysis of environmental literacy and awareness to maintain environmental sustainability - Mustofa, Ali; Sueb, Sueb (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2023)
Environmental damage is the effect of negative impacts on the natural environment caused by human activities. The importance of empowering knowledge and caring for the environment in students so that they can participate in protecting and preserving the environment. The purpose of this research is to describe literacy and environmental awareness to preserve the environment and the relationship between environmental literacy and awareness to preserve the environment. This research method uses descriptive quantitative research and research techniques using a questionnaire with a sample of 50 students using a random sampling technique in the Adiwiyata school program, especially junior high school students. The instruments used were student characteristic sheets, environmental literacy, and environmental awareness questionnaires. Research data were analyzed descriptively and the relationship between literacy and environmental awareness used correlation analysis using SPSS. The results showed that students' environmental literacy was classified as moderate to high with a score of 1.6 – 3.20. The average value of students' environmental awareness is 73% indicating that students have a caring attitude toward environmental problems. Environmental attitudes and environmental awareness also have a significant relationship (sig <0.05). Through environmental literacy and awareness, students will have the potential to protect and preserve the environment.